Feasibility study of MgSO4 + zeolite based composite thermochemical energy stores charged by vacuum flat plate solar thermal collectors for seasonal thermal energy storage. (January 2020) - Mahon, D.; Henshall, P.; Claudio, G.; Eames, P.C.
Abstract: A primary drawback of solar thermal technologies, especially in a domestic setting, is that collection of thermal energy occurs when solar irradiance is abundant and there is generally little requirement for heating. Thermochemical Energy Storage (TCES) offers a means of storing thermal energy interseasonally with little heat loss. A combination of a Solar Thermal Collector (STC) and TCES system will allow a variety of different heating applications, such as domestic space and hot water heating as well as low temperature industrial process heat applications to be met in a low carbon way. This paper describes and assesses the feasibility of two novel technologies currently under development at Loughborough University; i) an evacuated flat plate STC and ii) composite TCES materials, coupled together into a system designed to store and supply thermal energy on demand throughout the year. Experimental results of composite TCES materials along with predicted performance of STC's are used within a developed model to assess key metrics of conceptual TCES + STC systems feasibility, including; charging time, payback time, cost/kWh, energy savings and CO2 savings. This paper demonstrates the economic, energy and carbon savings potential of conceptual TCES + STC systems suitable for domestic use. Highlights: Economic feasibility of novel TCES + STC conceptual systems presented. Conceptual systems using a Vacuum Flat Plate Collector are the most economical. 30% of the domestic space heating demand can be supplied using these systems. Significant CO2 reductions possible if systems installed in UK households. Systems predicted to result in financial savings to the homeowner.